Beyond the Post: Exploring Equine Operators’ Understanding and Role in Conservation Best Management Practices - Anissa M. Zagonel; Lauri M Baker; Shelli Ingram; Jonathan D. Ulmer; Joann M. Kouba (Journal of Applied Communications, 2021)
The equine industry is an established part of Maryland agriculture with 79,100 equines valued at approximately $714 million in the state; approximately 10% of these animals are housed in one county. Equine operators are a unique demographic in the agricultural realm, because they are not managing land to produce food or fiber and often are employed in other professions unrelated to agriculture. These operators tend to be unaware of land conservation practices and can have a detrimental effect on areas, like the Chesapeake Bay economy and ecosystem, if shared resources are exploited. The purpose of this study was to explore equine operators’ knowledge and connection of conservation best management practices (BMPs) and their role in being a caretaker of the land. The study was informed by the diffusion of innovations theory and gathered data through semi-structured, qualitative interviews. Equine operators in the study were found to use a variety of informational sources, had a high level of adoption of the BMPs they used, and overall, a majority of participants saw their role as caretakers of the land as an important aspect of their environmental actions. Recommendations from this research include improving communication processes to increase the spread of BMPs and adjusting specific infrastructure aspects to improve retention of equine operators practicing conservation efforts. Further research should investigate other niche areas of agriculture that could potentially be struggling with a knowledge deficit of BMPs and communication neglect between conservation offices and audiences.
Keywords: best management practices; conservation; diffusion of innovations; information sources; strategic communication